The conventional conflict management system Red Book FIDIC -edition 1999- and its contribution of efficiency in the solution of conflicts in construction projects - Paredes, Gustavo (2018)
The author of this presentation intends to investigate the essence of international practice used in the resolution of disputes in this legal field, which is a source of necessary observation, highlighting that it is a matter of interest and study for those passionate in this area. It is proposed to provide the reader with knowledge that allows him to understand and compare its systematicity as its effects at the national level with other regulations in order to understand its application.